Penerapan Porter Five Forces Dan Analisis Swot Dalam Perencanaan Strategi PT Roves Global Food - Kevin Naufal Eryogia; Komang Diah Cahya Utami; Diajeng Siti Aqiilah Sundari; Alya Nadhifah Bintang; Wahyu Dharma Wibisana (EBISMAN eBisnis Manajemen, 2024)
Indonesia presents promising opportunities in the processed food industry, which has experienced a 5% growth over the past five years. PT Roves Global Food has leveraged this opportunity by utilizing mangrove-based products in their processed food offerings. This strategy aims to promote sustainable resources with high nutritional value. However, the company still faces challenges due to consumer trend dynamics, supply chain issues, and government regulations. This study aims to analyze the internal and external conditions of the company using Porter Five Forces analysis and SWOT. Data was collected through primary methods, such as interviews, and secondary sources. The Porter Five Forces analysis revealed five main external factors affecting the company: Threats of Substitutes, Threats of New Entrants, Intensity of Competitive Rivalry, Bargaining Power of Suppliers, and Bargaining Power of Buyers. Additionally, the SWOT analysis identified the strengths, weaknesses, opportunities, and threats for the company, resulting in 12 combination strategies: 4 SO, 2 ST, 4 WO, and 2 WT strategies. The analysis outcomes were then used to formulate key strategy recommendations focused on strengthening three of the five primary internal conditions of the company, namely service, marketing and sales, and operations.